Beyond Free Trade
XI, 305 p.
Keywords: The world of trade is changing rapidly, from the 'rise of the South' to the growth of unconventional projects like fair trade and carbon trading. Beyond Free Trade advances alternative ways for understanding these new dynamics, based on historical, political, or sociological methods that go beyond the limitations of conventional trade economics.